Preparation and characterization of poly (lactic acid) / poly (butylene succinate) / graphene oxide composite - Md Sukur, Nuraini (2017)
The present research study the effect of graphene oxide (GO) on the properties of poly(lactic acid)/poly(butylene succinate), (PLA/PBS). GO was synthesized from graphite through modified Hummers’ method. The synthesized GO was characterized using Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), and Thermogravimetric analysis (TGA). FTIR and XRD results proved that GO was successfully synthesized. XRD showed that a new broad peak at 12.9 ̊ emerged with the occurrence of graphite layer oxidation. PLA/PBS blends were prepared via melt blending technique. FTIR spectra revealed shifting of functional group peaks to lower wavenumber indicating chemical interaction occurred between PLA and PBS. Tensile strength and modulus decreased with increasing amount of PBS due to PBS elasticity. SEM micrographs of PLA/PBS blends showed immiscibility with more than 20 wt.% of PBS content. Thermal properties of PLA/PBS blend improved with the addition of PBS. From the mechanical and morphological studies, PLA with 20 wt.% PBS loading was chosen as optimum ratio and used for the preparation of PLA/PBS/GO composites. The PLA/PBS/GO composites were prepared via melt blending technique. The mechanical property of the composites improved with the addition of 0.1 wt.% of GO. Thermal analysis of the composites also revealed significant improvement in thermal stability compared to PLA/PBS blend and pristine PLA. SEM micrographs results revealed rougher surfaces when more GO loaded to the PLA/PBS blend. Furthermore, the PLA/PBS/GO composite with 0.1 wt.% GO loading was more water resistance than PLA/PBS blend because GO can act as barrier to the composite. Biodegradability test revealed that the PLA/PBS/GO has the lowest weight lost compared to PLA/PBS blend and neat PLA.